Diagnosis of Brucellosis in Livestock and Wildlife - Godfroid, Jacques (Croatian Medical Schools, 2010)
AIM: To describe and discuss the merits of various direct and indirect methods applied in vitro (mainly on blood or milk) or in vivo (allergic test) for the diagnosis of brucellosis in animals. METHODS: The recent literature on brucellosis diagnostic tests was reviewed. These diagnostic tests are applied with different goals, such as national screening, confirmatory diagnosis, certification, and international trade. The validation of such diagnostic tests is still an issue, particularly in wildlife. The choice of the testing strategy depends on the prevailing brucellosis epidemiological situation and the goal of testing. RESULTS: Measuring the kinetics of antibody production after Brucella spp. infection is essential for analyzing serological results correctly and may help to predict abortion. Indirect ELISAs help to discriminate 1) between false positive serological reactions and true brucellosis and 2) between vaccination and infection. Biotyping of Brucella spp. provides valuable epidemiological information that allows tracing an infection back to the sources in instances where several biotypes of a given Brucella species are circulating. Polymerase chain reaction and new molecular methods are likely to be used as routine typing and fingerprinting methods in the coming years. CONCLUSION: The diagnosis of brucellosis in livestock and wildlife is complex and serological results need to be carefully analyzed. The B. abortus S19 and B. melitensis Rev. 1 vaccines are the cornerstones of control programs in cattle and small ruminants, respectively. There is no vaccine available for pigs or for wildlife. In the absence of a human brucellosis vaccine, prevention of human brucellosis depends on the control of the disease in animals.